Inflammatory adipose activates a nutritional immunity pathway leading to retinal dysfunction - Jacob K. Sterling; Bailey Baumann; Sierra Foshe; Andrew Voigt; Samyuktha Guttha; Ahab Alnemri; Sam J. McCright; Mingyao Li; Randy J. Zauhar; Sandra R. Montezuma; Rebecca J. Kapphahn; Venkata R.M. Chavali; et al. (Cell Reports, 2022)
Summary: Age-related macular degeneration (AMD), the leading cause of irreversible blindness among Americans over 50, is characterized by dysfunction and death of retinal pigment epithelial (RPE) cells. The RPE accumulates iron in AMD, and iron overload triggers RPE cell death in vitro and in vivo. However, the mechanism of RPE iron accumulation in AMD is unknown. We show that high-fat-diet-induced obesity, a risk factor for AMD, drives systemic and local inflammatory circuits upregulating interleukin-1β (IL-1β). IL-1β upregulates RPE iron importers and downregulates iron exporters, causing iron accumulation, oxidative stress, and dysfunction. We term this maladaptive, chronic activation of a nutritional immunity pathway the cellular iron sequestration response (CISR). RNA sequencing (RNA-seq) analysis of choroid and retina from human donors revealed that hallmarks of this pathway are present in AMD microglia and macrophages. Together, these data suggest that inflamed adipose tissue, through the CISR, can lead to RPE pathology in AMD.